Yos Sebagai Pengintegrasian Masyarakat Desa Pedawa - Arik Febriani, Ni Putu; Suwena, I Wayan; ., Aliffiati (Humanis, 2020)
Pedawa Village community, Banjar sub-district, Buleleng Regency has two kawitan namely kulit and kawitan lokal. Kawitan kulit that found in Pedawa Village is the general kawitan in Bali, meanwhile kawitan loca l of the Pedawa Village community refers to Yos which must be owned by all Pedawa Village communities. The Yos has a highly glorified God and the god closest to the community because the God is believed to be a protective deity, with the existence of the Yos the formation of social class in society. This reserach aimed to know the status and role of community members based on Yos, and to reveal the implications of Yos for the social structure of the Pedawa Village community. The results of the study revealed that there were 14 types of Yos. From several types of Yos, there are several members of community who have the status and role in a ceremony namely as Balian Desa, Premas, Headman , Janbangul, Pedewasan, and Sekaa Gong. Yos also has important implications and meanings toward the Pedawa Village community. T he implications of Yos on aspects of the pedawa Village community belief system, besides the implications there are also meanings of Yos covering religious meaning , social meaning and cultural meaning.